A System for Management of Urbanized Areas in the Aspect of Acoustic Effects - KOMPAŁA, Janusz (Archives of Acoustics, 2011)
Within the boundaries of many municipal urbanized areas, large grounds arefound, from which the noise is emitted into the environment, surrounded by theregions liable to acoustic protection. Such a condition generates many problemsincluding also those ones related to the lack of the fulfillment of requirements concerningenvironmental protection against excessive noise. Therefore the aim of vitalimportance is the proper management of municipal grounds, both in view of theinvestment in policy steering, especially of new investments, and in the case of activitiesaimed at maintaining or restoring (revitalizing) the acoustic properties onthe grounds that have already been used or simply degraded before.Keeping the scale of the problem in mind, such activities must be carried onnot temporarily, but must have a systemic character. The structure of every systemis characterized by the appropriate relationships among their elements and theproperties of those relationships. In case of the noise management system, the elementsof such a system are the activities connected with the management itselfthat are the actions which rely on specifying the aims and causing their realizationwithin the scope and on the grounds subject to the managing entity. The superioraim of such activities should be to supply the tools for improvement of managementand in the process of taking decisions that relate to investments including theof optimization conditions and maintenance of socio-economic importance of suchareas.